Does education level affect the health status of the elderly? The chain mediating effect of internet use, health behavior and social class identity - Ting Qin; Pingqiang Wei; Yuanyuan Xie (PLoS ONE, 2025)
Background China’s aging population is gradually increasing, and the health status of the elderly has become the focus of social attention. Education level is one of the important factors affecting the health status of the elderly. However, there are few studies on how education level specifically affects the health status of the elderly in China. Therefore, the purpose of this study is to explore the influence path of education level on the health status of the elderly in China, and to further study the mediating effect of Internet use, health behavior and social class identity in this process. Methods This study is based on the latest version of the Chinese General Social Survey data as the basis of empirical analysis. Through multiple linear regression analysis, structural equation model analysis, Bootstrap method and robustness test, the relationship between education level, Internet use, health behavior, social class identity and the health status of the elderly is verified. Results (1) Education level has a significant positive impact on the health status of the elderly in China (p < 0.05), which is, education level has a positive effect on the health status of the elderly in China. (2) Internet use, health behavior and social class identity have a significant mediating effect between education level and health status of Chinese elderly, and the mediating effect values are 0.024, 0.002 and 0.011, respectively. (3) Internet use, health behavior and social class identity play a chain mediating role in the impact of education level on the health status of the elderly, and the chain mediating effect value is 0.004. Conclusions This study not only confirms the direct impact of education level on the health status of the elderly in China, but also reveals the indirect role of Internet use, healthy behavior and social class identity in this impact mechanism. These findings provide new perspectives and strategies for further improving the health status of the elderly in China.